Paisagem cultural, turismo e gestão da paisagem: estudo dos distritos de Milho Verde e São Gonçalo do Rio das Pedras - Serro/Minas Gerais - Elcione Luciana da Silva (2015)
The evolution of the concept of cultural heritage has created a further reflection on the identification of properties relevant for humanity and requiring new policies for their preservation. The protection of heritage that before was limited to tangible and intangible cultural assets, has come to include other elements essential for the protection of cultural heritage in line with other sector policies, also seeking integrated conservation of cities (urban and environmental heritage). Thus, not only the built heritage becomes an object of conservation, but also its surroundings, relations between human and nature being thus taken into consideration. With the evolution of the study of the relationships between the landscape and humans, a new concept of landscape as a result of human action arises, in the notion of cultural landscape. Within this context the discussions regarding the preservation of the landscape began to be rethought in order to readjust to a new reality and the demands of this new concept, especially regarding the preservation of the sites listed as World Heritage Sites. The inclusion of the category of Cultural Landscape by UNESCO in 1992 brought about new possibilities for the study of man's relationship with his environment. This research aims to address the evolution of the cultural landscape concept and the difficulties of management and protection of these cultural landscapes, taking as objects of study the Milho Verde communities and São Gonçalo do Rio das Pedras, in the district of Serro / MG. Both locations hold tourism as an economic alternative and have characteristics that classify these communities as Cultural Landscapes. These communities have emerged as a result of the mining of precious stones by the Portuguese Crown during the colonial period and managed to preserve significant elements of the first seventeenth century villages that emerged at the height of the mining activity. Both communities underwent few changes in relation to their architectural ensemble and the environment, being characterized as places of memory and becoming important examples of man's relationship with the natural environment. With further discussions involving the relationship between landscape and culture, new challenges for the management and protection of the Cultural Landscape arise, requiring preservation policies to include in the discussions the protection of the landscape, considering all the aspects involved in it (man, nature, tangible and intangible heritage). These communities, however, have been facing in recent years different processes of occupation, with the arrival of new residents motivated by the scenic beauty and natural resources in the region, as well as the increase of tourist flow, factors that can interfere in various ways in the cultural landscape or contribute for its reconstruction.